IMPLEMENTATION OF THE "KRAME VILLAGE" TRADITIONAL LAW IN RESOLVING THE CRIME OF THEFT IN THE SASAK TRIBE COMMUNITY (Study in Sade Traditional Tourism Village, Central Lombok) - Novi Komalasari; Abdul Majid; Iwan Permadi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The Krame Desa tradition as an alternative solution to criminal acts of theft in the Sasak tribal community in Central Lombok. The background to the choice of this theme was the existence of a mechanism for resolving criminal acts of theft among the Sasak Traditional Law community in the Sade Traditional Tourism Village, called Krame Desa. Krame Desa is an activity carried out by two or more people and a group of people to determine who is wrong and right in terms of defending the property rights of one person or many people by drinking the ground water from the grave of the guardian of Nyatuk. Based on the above, this paper raises the formulation Problem: How is the implementation of the "Krame Desa" Customary Law in resolving criminal acts of theft among the Sasak tribe community in the Sade Traditional Tourism Village, Central Lombok Regency? What is the Strength of the Decision to Settle the Crime of Theft Through the Village Temple in the Sade Traditional Tourism Village, Central Lombok Regency? Then this paper was written using empirical research using a sociological juridical approach and a case approach. The research location is in the Sade Traditional Tourism Village, Pujut District, Central Lombok. The data obtained by the author consisting of primary and secondary data will be analyzed using qualitative descriptive analysis techniques. The results of this research show that the meaning of Krame Desa is a mechanism for resolving disputes in the Sasak Customary Law community, especially in criminal acts of theft, where the philosophical basis is to restore magical and spiritual balance in society, in the process using oaths.